2015
DOI: 10.1007/s10689-015-9855-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between allergic conditions and pediatric brain tumors in Neurofibromatosis type 1

Abstract: Background Individuals with Neurofibromatosis type 1 (NF1) are at increased risk for pediatric brain tumors (PBTs), especially optic gliomas; however, factors influencing their development are largely unknown. Extensive research suggests that allergic conditions protect against brain tumors, particularly gliomas in individuals without NF1. In this large cross-sectional study, we employed two different data sources to evaluate evidence for the hypothesis that allergic conditions (allergies, asthma, and eczema) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Collectively, these findings indicate that the biological behavior of these tumors is heavily influenced by a myriad of factors, which each might be actionable. As such, the ability to incorporate sex and the germline NF1 gene mutation in combination with other factors, like asthma and genomic background, [77][78][79][80] into predicable risk assessment models is likely to improve our ability to manage children at risk for NF1-OPG. In addition, some of these factors may yield actionable outcomes, including new therapeutic approaches.…”
Section: Future Directionsmentioning
confidence: 99%
“…Collectively, these findings indicate that the biological behavior of these tumors is heavily influenced by a myriad of factors, which each might be actionable. As such, the ability to incorporate sex and the germline NF1 gene mutation in combination with other factors, like asthma and genomic background, [77][78][79][80] into predicable risk assessment models is likely to improve our ability to manage children at risk for NF1-OPG. In addition, some of these factors may yield actionable outcomes, including new therapeutic approaches.…”
Section: Future Directionsmentioning
confidence: 99%
“…A retrospective case review was conducted to identify individuals with NF1 and melanoma following approval by the Washington University Institutional Review Board spanning visits between July 1997 and July 2017. We used a previously compiled neurofibromatosis patient medical record registry [14][15] as the initial patient cohort and added additional patients seen during the expanded study period. We used a REDCap database (https://projectredcap.org/software/) to capture all study data.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Porcelli et al in a cross‐sectional study reported that allergic disorders may protect against pediatric brain tumors (PBTs) development in individuals with Neurofibromatosis type 1. In another study, a nonsignificant inverse relationships between asthma and PBTs were reported, although this association was stronger in the younger than in the older age group 139 . Brenner et al in a multicenter hospital‐based study among adults reported a 2.4‐fold increased risk of having a history of hay fever for acoustic neuroma (95% CI: 1.4 to 4.0) 60 …”
Section: Allergy and Cancer Riskmentioning
confidence: 96%
“…In another study, a nonsignificant inverse relationships between asthma and PBTs were reported, although this association was stronger in the younger than in the older age group. 139 Brenner et al in a multicenter hospitalbased study among adults reported a 2.4-fold increased risk of having a history of hay fever for acoustic neuroma (95% CI: 1.4 to 4.0). 60 Overall, the evidence, suggests that allergic diseases appear to be associated with a lower risk of brain tumors (Tables 1 and 2).…”
Section: Brain Cancermentioning
confidence: 97%